Weaning of inhaled nitric oxide: is there a best strategy? - Anita M. Ware; Sergio G. Golombek (Hygeia Press di Corridori Marinella, 2015)
Background: Inhaled nitric oxide (iNO) has been used in the treatment of pulmonary hypertension in neonates for many years. iNO was approved by the FDA in 1999 for hypoxic respiratory failure (HRF) in term and near term infants, defined as > 34 weeks gestational age (GA). iNO is used for persistent pulmonary hypertension of the newborn (PPHN), secondary pulmonary hypertension caused by congenital heart disease (CHD), congenital diaphragmatic hernia (CDH), meconium aspiration syndrome (MAS), pneumonia, respiratory distress syndrome (RDS), and other pathologies. iNO has its effect locally on the pulmonary vasculature and has been studied extensively regarding its effect on morbidities such as: need for extracorporeal membrane oxygenation (ECMO), oxygen requirements, and mechanical ventilatory support. However, protocols for weaning iNO and for the duration of iNO weaning have not been studied extensively. It has been shown that an abrupt discontinuation leads to rebound pulmonary hypertension. Methods: Electronic literature search and review of published articles on the use of iNO in the neonate. Results: Electronic databases including Medline and PubMed were searched from the years 1995-2015, using the keywords "iNO", "nitric oxide", "neonate", and "weaning nitric oxide." This search revealed 2,124 articles. Articles were determined to be eligible for review if they included a specific protocol for weaning iNO, and were published in English. 16 articles with specific protocols for iNO weaning have been identified and reviewed. The studies had enrolled a total of 1,735 neonates either at term either preterm and with a mean birth weight of 3.3 kg (± 2 kg). Main diagnoses included MAS, CHD (total anomalous pulmonary venous return [TAPVR], d-transposition of the great vessels [DTGV], atrial septal defect [ASD], pulmonary atresia [PA], hypoplastic left heart syndrome [HLH]), pneumonia, RDS, hyaline membrane disease (HMD), PPHN, CDH, sepsis, pulmonary hypoplasia, pulmonary hemorrhage, hydrops fetalis, and other congenital anomalies. The average dose of iNO was 20 ppm (range = 2-80 ppm). The duration of exposure to iNO was on average 2 ± 2 days (range = 15 min - 7 days). Weaning protocols were highly varied from duration of treatment, duration of time in between iNO decreases, initial dose, adjunctive medications used to wean, and increasing FiO2 used to wean iNO. The weaning parameters were based on multiple variables including FiO2, PaO2, O2 sats, and pulmonary arterial pressure. Conclusion: There is a limited amount of data specific to weaning protocols for nitric oxide. There is no consensus on an appropriate method for weaning of iNO either on its own, or with adjunct medication. Further research to elucidate a strategy for weaning of iNO needs to be done. We propose that weaning iNO in a stepwise approach from 20 ppm in increments of 5 ppm per decrease until 5 ppm; and stepwise by 1 ppm from 5 ppm to off, while monitoring O2 saturations and blood gases parameters and allowing transient increases in FiO2 during adjustment to the transition is a safe approach (both for invansive and non-invasive modes of ventilation). This is not a protocol that is appropriate for every patient pathology, but is a safe starting point with allowance for individual patient and physician variablilty.